Identification of a ligand-binding site on the Staphylococcus aureus DnaG primase C-terminal domain - Catazaro, Jonathan (Biochemistry, 2017)
The interface between the DnaG primase C-terminal domain (CTD) and the N-terminal domain of DnaB helicase is essential for bacterial DNA replication because it allows coordinated priming of DNA synthesis at the replication fork while the DNA is being unwound. Since these two proteins are conserved in all bacteria and distinct from those in eukaryotes, their interface is an attractive antibiotic target. To learn more about this interface, we determined the solution structure and dynamics of the DnaG primase CTD from Staphylococcus aureus, a medically important bacterial species. It has two subdomains like the primase CTD structures from other bacteria in which the first six helices create the C1 subdomain and the last two helices, 7 and 8, create the C2 subdomain. Comparison with the known primase CTD structures shows there are two biologically relevant conformations – an open conformation that likely binds to DnaB helicase and a closed conformation that does not. The S. aureus primase CTD is in the closed conformation, but NMR dynamic studies indicates there is considerable movement in the linker between the two subdomains and that N564 is the most dynamic residue within the linker. A high-throughput NMR ligand-affinity screen identified potential binding compounds, among which were acycloguanosine and myricetin. Although the affinity for these compounds and adenosine was in the millimolar range, all three bind to a common pocket that is only present on the closed conformation of CTD. This binding pocket is at the opposite end of helices 6 and 7 from N564, the key hinge residue. The identification of this binding pocket should allow the development of stronger-binding ligands that can prevent formation of the CTD open conformation that binds to DnaB helicase.